(untitled) (Huellas, 2019)
Religion is a topic of growing interest within the agenda of Latin American historians and geographers. The objective of this work is to contribute to the historic analysis of the religious situation in Argentina, through the consideration of the case of La Pampa. Based on the information provided by the national censuses and the National Register of Religions, we present a historical study on the religious diversity in this province during the 20th and 21st centuries. In particular, we observe the changes and continuities of the Protestant traditions and the rise of new evangelical expressions in a territory that was belatedly incorporated into the National State and marked by the processes of reoccupation and repopulation after the 1880s.